PERBUATAN MELAWAN HUKUM BANK DALAM LELANG HARTA WARISAN SEBAGAI JAMINAN DENGAN HAK TANGGUNGAN PERSPEKTIF KEADILAN - I Gusti Ngurah Anom (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
The role of banks is very important in economic development in Indonesia, especially for people who have business skills but are hampered by a lack of capital, so they need financial assistance to run their business smoothly. In accordance with the Law of the Republic of Indonesia No: 10 of 1998 concerning Banking, it is stated that when providing credit to the public, the 5 C elements must be taken into account, namely Capacity, Collateral, Character, Capital and Economic Conditions. To guarantee the safety of returning credit to the bank, the debtor is required to provide collateral to the bank, so that if the debtor is unable to repay the debt, the collateral will be sold/auctioned. In carrying out the auction of collateral objects, disputes often arise between the bank and the debtor, especially since the debtor who signed the credit agreement has died and the inheritance left behind has become collateral at the bank which is burdened with Mortgage Rights. Debtors often argue that the auction action carried out by the bank is an act against the law, as in the Civil Case Decision at the Denpasar District Court No: 1299/Pdt.G/2024/PN.DPS.The issue being discussed is whether submitting an auction by the bank for debt collateral is an unlawful act, then how is the heirs' fair protection for inherited assets as debt collateral being auctioned by the bank. The research method used is normative legal research The results of the research show that the legal protection for the debtor if the collateral is auctioned is to return the remainder of the auction proceeds to the debtor if there is still any remaining after deducting all the debtor's obligations. The auction carried out by the bank for collateral objects owned by the debtor is not an unlawful act because it is in accordance with applicable regulations